Case Study: KFC Puncak Alam / Mohd Izwan Abu Bakar, Nuur Aina Farhana Ahmad Rosli and Sitinurfaten Abu Bakar - Abu Bakar, Mohd Izwan; Ahmad Rosli, Nuur Aina Farhana; Abu Bakar, Sitinurfaten (2020)
KFC is a fast food restaurant specializing in Original Recipe fried chicken. KFC in Puncak Alam is popular among student because it is located near to UiTM Campus Puncak Alam and local resident near there and the only one of KFC store in Puncak Alam.